hsa_circ_0072309 Expression Profiling in Non-small-Cell Lung Carcinoma and Its Implications for Diagnosis and Prognosis - Zhou, Yong; Tong, Zhongkai; Zhu, Xiaoxiao; Huang, Shaoqing; Dong, Zhaoxing; Ye, Zhenyue (Frontiers in Surgery, 2022)
Abstract: Circular RNAs (circRNAs), which fall into the category of endogenous ncRNAs, are linked to disease progression of neoplastic diseases. Whereas, it remains uncharacterized regarding hsa_circ_0072309’s function and implications in lung carcinoma (LC). Gene Expression Omnibus (GEO) database was utilized for identifying circRNAs with aberrantly expression in LC. qRT-PCR was responsible for determining hsa_circ_0072309 levels in lung adenocarcinoma (LAC). Also, its involvement in LC cell progression was investigated. Experimentally, hsa_circ_0072309 was identified as one of the most aberrantly down-regulated circRNAs in the GEO database (GSE101684 and GSE112214). qRT-PCR revealed notably down-regulated hsa_circ_0072309 in LAC tissue, which had a close association with adverse 3-year survival, as well as LNM and advanced TNM stage. Based on ROC, the AUC of hsa_circ_0072309 was determined to be 0.887, and its specificity and susceptibility can be improved by combined detection of either CYFRA21-1 or CEA. In a word, expressed at low levels in NSCLC, hsa_circ_0072309 is strongly associated with patient outcomes, which is a candidate marker with prognostic utility for the disease.